Fernsehen ist gestern: Medienhistorische Transformationen und televisuelles Dabeisein nach 1945 - Bernold, Monika (Österreichische Zeitschrift für Geschichtswissenschaften, 2001)
The author outlines a number of conceptual approaches from media studies that are of interest for television history. In combining media studies and historical science perspectives, she argues for the historicisation of television and for the use of media studies theory in historical approaches to the subject. Taking J. Ellis' concept of >witness< as a starting point, the author utilizes the notion of eyes/time/witnessing in order to locate television in a complex relationship to history and memory. She describes television as a dispositive means of assigning a sense of belonging; the different historical forms that this process takes must then be considered as of fundamental importance to a history of collective mentalities and representations since 1945. By drawing on examples from the history of television in Austria in the 1960s, 1970s and 1990s, the author goes on to demonstrate how television was able to generate different forms of televisual »being there « (a »Television National «, a TV-based community of remembering, a cultural memory of the banal), which corresponded closely with the development of changing media landscapes.